Perceived Health Concerns of Child Thirdhand Smoke Exposure and Potential Remediation Strategies Among Nonsmoking Parents of Young Children - E. Melinda Mahabee-Gittens; Georg E. Matt; Lara Stone; Madelyn J. Hill; Ashley L. Merianos (Health Behavior Research)
We examined nonsmoking parents’ concerns about child thirdhand smoke exposure (THSe) and their likelihood of implementing remediation strategies based on hypothetical handwipe nicotine (HN) levels, a proxy for children’s THSe levels. Parents (N=245) of 0-11-year-old children were told that “low” and “high” HN levels were 10ng/wipe and 200ng/wipe, respectively. Parents reported higher mean concern that THSe would affect their child’s health (M=2.3, SD=1.1) and were more likely to implement THSe remediation strategies (M=2.7, SD=0.7) when presented with high HN levels compared to low HN levels (M=1.5, SD=1.0, p<0.001, and M=2.0, SD=1.0, p<0.001, respectively). The top three endorsed remediation strategies for high and low HN levels were deep cleaning or professionally cleaning the home (78.8% and 63.7%) and not allowing smokers to smoke in the home (72.7% and 67.3%) and car (72.7% and 67.3%). Given nonsmoking parents’ concerns about THSe-related health risks, THSe education is needed among nonsmoking households with children.